Raf-kinase inhibitor protein attenuates microglia inflammation in an in vitro model of intracerebral hemorrhage - Wang, J; Du, J; Miao, C; Lian, H (Cellular and Molecular Biology, 2016)
Microglia mediated neuroinflammation plays a crucial role in intracerebral hemorrhage (ICH). Raf kinase inhibitor protein (RKIP), a member of the phosphatidylethanolamine-binding protein (PEBP) family, is a negative regulator of inflammatory responses. However, the expression and anti-inflammatory effects of RKIP in microglia after ICH have not been reported. Therefore, in the current study, we investigated the effects of RKIP on inflammatory responses in erythrocyte lysate-treated BV2 microglia. Furthermore, we analyzed the detailed molecular mechanisms underlying the anti-inflammatory effects of RKIP in microglia. Our results showed that the expression level of RKIP was significantly decreased by erythrocyte lysate treatment in BV2 microglia. Overexpression of RKIP inhibited the production of pro-inflammatory molecules. In addition, overexpression of RKIP attenuated neuronal cell death induced by activated microglia. Moreover, RKIP suppressed the activation of NF-ÎºB signaling pathway in erythrocyte lysis-treated BV2 cells. In conclusion, these data suggest that overexpression of RKIP attenuated microglia inflammation through inhibiting the NF-ÎºB signaling pathway in erythrocyte lysis-treated BV2 cells. The present study provides evidence that RKIP may be used as an effective molecular target for the treatment of ICH.